Synthesis of novel sulfonated poly(arylene ether)s containing a tetra-trifluoromethyl side chain and multi-phenyl for proton exchange membrane fuel cell application. Issue 53 (29th June 2017) - Huang, Yi-Chiang; Lee, Hsu-Feng; Tseng, Yu-Chao; Lee, Chun-Che; Chang, Mei-Ying; Huang, Wen-Yao
Abstract : Herein, a series of novel sulfonated poly(arylene ether)s consisting of tetra-trifluoromethyl-substituted multi-phenyl was synthesized and post-sulfonated to obtain sulfonated polymers with ion exchange capacities ranging from 1.27 to 2.53 mmol g −1 . Abstract : Herein, a series of novel sulfonated poly(arylene ether)s consisting of tetra-trifluoromethyl-substituted multi-phenyl was synthesized via polycondensation, and post-sulfonation was carried out through chlorosulfonic acid to obtain sulfonated polymers possessing ion exchange capacities ranging from 1.27 to 2.53 mmol g −1 . 1 H NMR and FTIR spectroscopy were applied to confirm the structure and composition of the sulfonated polymers. The membranes exhibited considerable dimensional stability (with 3.1–27.8% change in length; 17–56.5% change in thickness at 80 °C) and excellent oxidative stability (weight remained higher than 97%). The mechanical properties of the membranes demonstrated good tensile strength on account of the highly rigid multi-phenylated backbone, and Young's modulus ranged from 0.65 to 0.88 GPa. The proton conductivities of the membranes ranged from 0.03 to 0.24 S cm −1 at 80 °C under 95% RH, which were comparable to or higher than those of Nafion 211. The morphology of the membranes demonstrated a clear hydrophilic/hydrophobic phase separation with spherical ionic clusters in the size range of 5–20 nm. SFC2-2.53 demonstrated a high current density (around 1800 mA cm −2 at 0.6 V) and the maximum power density of 1.41 W cm −2 for the fuel cell performance. The results indicated that SFC2 would be a good candidate for proton exchange membranes in fuel cell applications.